2011
DOI: 10.1007/s10266-011-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization morphology and dentin bond stability of self-etch primers with different ethanol/water ratios

Abstract: This study evaluated the influence of ethanol/water ratios on the bond strength to dentin of experimental two-step, self-etch adhesive systems. Self-etch primers were prepared with constant 40 mass % of solvents. The ethanol/water ratios tested were 7:1 (P1), 3:1 (P2), and 1:1 (P3); primers with only ethanol (PE) or water (PW) as solvent were also tested. The bond strength to the dentin was investigated through a microtensile bond strength test. Resin-dentin beam-shaped specimens were obtained and tested after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Previous studies showed that long-term storage in water and other aging conditions may affect the durability of the dentin bonds 13,16,25,29 . The breakdown of the adhesive interfaces was related to loss of stability of the polymer components of the adhesive assembly 4,9,30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that long-term storage in water and other aging conditions may affect the durability of the dentin bonds 13,16,25,29 . The breakdown of the adhesive interfaces was related to loss of stability of the polymer components of the adhesive assembly 4,9,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The instability of the adhesion of restorative biomaterials to dentin has been demonstrated in vitro 1,13-16,24,25,30 . Degradation is known to possibly occur in the dentin substrate and/or in the polymer component of the restoratives 3,4,13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ethanol is the most commonly used organic hydrophilic solvent that is used either alone or with water as a co-solvent in various commercially available dental adhesives. For a durable bond, it is imperative that the organic solvents of the adhesive primers evaporate from the site of application because the retention of organic solvents may have a deleterious effect on the bonding of the resin-based materials to the substrate [16].…”
Section: Introductionmentioning
confidence: 99%